2018
DOI: 10.1093/eep/dvy002
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-disrupting chemicals, epigenetics, and skeletal system dysfunction: exploration of links using bisphenol A as a model system

Abstract: Early life exposures to endocrine-disrupting chemicals (EDCs) have been associated with physiological changes of endocrine-sensitive tissues throughout postnatal life. Although hormones play a critical role in skeletal growth and maintenance, the effects of prenatal EDC exposure on adult bone health are not well understood. Moreover, studies assessing skeletal changes across multiple generations are limited. In this article, we present previously unpublished data demonstrating dose-, sex-, and generation-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 88 publications
1
15
0
Order By: Relevance
“…Xin et al (2018) demonstrated dose-, sex-, and generation-specific differences in skeletal morphology and mechanical function following gestational and lactational exposure to BPA. The lateral growth of the femur was affected depending on sex and dose, while there was no change in the longitudinal growth of the femur.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Xin et al (2018) demonstrated dose-, sex-, and generation-specific differences in skeletal morphology and mechanical function following gestational and lactational exposure to BPA. The lateral growth of the femur was affected depending on sex and dose, while there was no change in the longitudinal growth of the femur.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, this study may be the first reported research in this area. Apart from this, studies that examined the effects of BPA on bone development following prenatal exposure have shown a delay in ossification, skeletal disorders, and increased femur length (Agas et al, 2013; Kim et al, 2001; Xin et al, 2018). Hardin et al (1981) reported that 85- and 125-mg/kg doses of BPA reduced the number of live fetuses and suppressed fetal BW and head-to-shoulder length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When given during gestation, BPA appears to have sex-and dose-dependent results. Almost no studies showed any differences in female offspring of BPA-exposed dams compared to control offspring [61][62][63][64]. In rats, male offspring had increased cortical thickness at the 25 µg dose compared to control, but decreased cortical thickness at the 250 µg dose [61].…”
Section: Bpa and Bonementioning
confidence: 98%
“…In mice, male offspring had increased femur lengths, but no differences in biomechanical strength [63]. In another study in mice, male offspring showed decreased cortical thickness and biomechanical strength regardless of dose [64]. In addition to animal models, BPA exposure blocks osteoblastic and osteoclastic differentiation and increases markers of apoptosis in a dosedependent manner in progenitor cells [65] and human osteosarcoma cells [66].…”
Section: Bpa and Bonementioning
confidence: 99%